Psychological and neurophysiological measures of emotion dysregulation in borderline personality disorder and posttraumatic stress disorder - Göhre, Isabelle; Back, Sarah; Schütz-Bosbach, Simone; Ren, Qiaoyue; Wolkenstein, Larissa; Rupp, André; Bertsch, Katja (Borderline Personality Disorder and Emotion Dysregulation, 2025)
Emotion dysregulation is a central feature in trauma-associated disorders such as posttraumatic stress disorder (PTSD) and borderline personality disorder (BPD). However, it remains unclear whether emotion dysregulation is a transdiagnostic phenomenon closely linked to childhood trauma, or if disorder-specific alterations in emotion processing exist. Following a multimethodological approach, we aimed to assess and compare the reactivity to and regulation of emotions between patients with BPD and PTSD, as well as healthy controls, and identify associations with childhood trauma.